Hydrogel microrobots for biomedical applications - Song, Wenping; Li, Leike; Liu, Xuejia; Zhu, Yanhe; Yu, Shimin; Wang, Haocheng; Wang, Lin (Frontiers in Chemistry, 2024)
Recent years have witnessed a surge in the application of microrobots within the medical sector, with hydrogel microrobots standing out due to their distinctive advantages. These microrobots, characterized by their exceptional biocompatibility, adjustable physico-mechanical attributes, and acute sensitivity to biological environments, have emerged as pivotal tools in advancing medical applications such as targeted drug delivery, wound healing enhancement, bio-imaging, and precise surgical interventions. The capability of hydrogel microrobots to navigate and perform tasks within complex biological systems significantly enhances the precision, efficiency, and safety of therapeutic procedures. Firstly, this paper delves into the material classification and properties of hydrogel microrobots and compares the advantages of different hydrogel materials. Furthermore, it offers a comprehensive review of the principal categories and recent innovations in the synthesis, actuation mechanisms, and biomedical application of hydrogel-based microrobots. Finally, the manuscript identifies prevailing obstacles and future directions in hydrogel microrobot research, aiming to furnish insights that could propel advancements in this field.